IoT-Based Solar Power Plant Parameter Monitoring System - Azwa Soleha; Jefri Lianda; Adam (International Journal of Science and Environment (IJSE), 2026)
The utilization of Solar Power Plants (plts) as a renewable energy source continues to increase in line with the growing demand for environmentally friendly energy. However, the performance of an SPP is highly influenced by environmental conditions and variations in its electrical parameters. Therefore, a monitoring system capable of providing real-time information and remote access is required. This study aims to design and implement an Internet of Things (IoT)-Based Solar Power Plant Parameter Monitoring System to monitor key parameters such as voltage, current, power, and solar panel temperature. The system uses an ESP32 microcontroller as the main processing unit connected to various measurement sensors. The collected data are transmitted through the internet to a monitoring platform, allowing users to observe the condition of the solar power plant in real time using mobile devices or computers. System testing was conducted to evaluate sensor reading performance, data communication stability, and overall monitoring system functionality. Data collection was carried out from a Solar Power Plant (SPP) between 09:00 AM and 03:00 PM. The results showed that the system was able to monitor and transmit solar power plant parameters in real time with good accuracy and reliability. The implementation of IoT technology in this monitoring system is expected to improve maintenance efficiency, reduce the risk of system failures, and support the optimization of solar power plant performance in generating electrical energy.